Application of Guided Inquiry Model with PASAGI Media to Improve Learning Outcomes on Cell Material - Hikam, Syifa Maharani; Kurniasih, Surti; Rozalina, Devi Putri (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2023)
Background: Social discrimination based on a person's ethnic and cultural background still often occurs in Indonesia, this is due to feelings of superiority as someone with a better background. There is a need to introduce culture and ethnicity through classroom learning, and low student learning outcomes are often found in cell material because this material is an abstract concept for students. Methods: Data collection uses test and non-test instruments, test instruments in the form of multiple choice questions and non-test instruments through response questionnaires. The data obtained was then analyzed using the Microsoft-Excel application. Results: Based on the data analysis that has been carried out, student learning outcomes increase and the N-gain value in cycle 1 is 79.36 and in cycle 2 is 89.39 with effective criteria. The student response questionnaire analyzed in cycle 1 as a whole had good criteria and in cycle 2 as a whole had very good criteria. Conclusion: The application of the inkuiri terbimbing model using PASAGI media can effectively improve student learning outcomes. Keywords : guided inquiry; PASAGI; learning outcomes